2021
DOI: 10.1136/bmjresp-2020-000800
|View full text |Cite
|
Sign up to set email alerts
|

Reflexive thematic analysis exploring stakeholder experiences of virtual pulmonary rehabilitation (VIPAR)

Abstract: IntroductionTo enable greater availability of pulmonary rehabilitation (PR), video-conferencing technology was employed to link a community site to a standard outpatient PR service to deliver the programme closer to those with chronic respiratory disease. The service was called virtual pulmonary rehabilitation (VIPAR). To understand the experiences of those involved in this service, this study aimed to answer the question: How do the different stakeholders that interact with VIPAR experience the programme?Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Perceived usefulness refers to the degree to which a person believes the digital health intervention could improve or enhance their ability to manage their condition and is a core determinant of sustained engagement [72]. For example, patients may feel that a digital approach will impinge on the benefits of face-to-face contacts, as they may no longer have physical access to HCPs for support and direction [71,73]. Interestingly, research has found that patients with COPD perceive several potential benefits arising from digital approaches to support self-management which suggests there are cohorts of patients already primed to adopt them [74].…”
Section: A Barriers and Facilitators To Adoption: Patient Perspectivementioning
confidence: 99%
See 3 more Smart Citations
“…Perceived usefulness refers to the degree to which a person believes the digital health intervention could improve or enhance their ability to manage their condition and is a core determinant of sustained engagement [72]. For example, patients may feel that a digital approach will impinge on the benefits of face-to-face contacts, as they may no longer have physical access to HCPs for support and direction [71,73]. Interestingly, research has found that patients with COPD perceive several potential benefits arising from digital approaches to support self-management which suggests there are cohorts of patients already primed to adopt them [74].…”
Section: A Barriers and Facilitators To Adoption: Patient Perspectivementioning
confidence: 99%
“…Training and resource barriers are also commonly cited by HCPs [73,76]. Research evaluating HCP's perspectives regarding a virtual PR programme found that more preparation and training time is needed to empower them to identify and address technical issues when they arise [73].…”
Section: B Barriers and Facilitators To Adoption: The Hcp Perspectivementioning
confidence: 99%
See 2 more Smart Citations